2016
DOI: 10.1371/journal.pgen.1006341
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring of Heterochromatin to the Nuclear Lamina Reinforces Dosage Compensation-Mediated Gene Repression

Abstract: Higher order chromosome structure and nuclear architecture can have profound effects on gene regulation. We analyzed how compartmentalizing the genome by tethering heterochromatic regions to the nuclear lamina affects dosage compensation in the nematode C. elegans. In this organism, the dosage compensation complex (DCC) binds both X chromosomes of hermaphrodites to repress transcription two-fold, thus balancing gene expression between XX hermaphrodites and XO males. X chromosome structure is disrupted by mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 64 publications
8
60
0
Order By: Relevance
“…Furthermore, morc-1 and hrde-1 RNAi caused a small, but significant, rescue of the male lethality triggered by aberrant targeting of the DCC to the single X chromosome in males (Carmi et al, 1998; Miller et al, 1988; Petty et al, 2009) ( morc-1 vs. vector: p =0.0053, hrde-1 vs. vector: p =0.0018, student’s t-test) (Figure 4G). The magnitude of rescue achieved by knockdown of morc-1 or hrde-1 is similar to that observed with loss of H3K9 methylation (Snyder et al, 2016). RNAi against dpy-27 , which encodes a DCC component, induced a more substantial rescue of male lethality, as expected (Meyer and Casson, 1986).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, morc-1 and hrde-1 RNAi caused a small, but significant, rescue of the male lethality triggered by aberrant targeting of the DCC to the single X chromosome in males (Carmi et al, 1998; Miller et al, 1988; Petty et al, 2009) ( morc-1 vs. vector: p =0.0053, hrde-1 vs. vector: p =0.0018, student’s t-test) (Figure 4G). The magnitude of rescue achieved by knockdown of morc-1 or hrde-1 is similar to that observed with loss of H3K9 methylation (Snyder et al, 2016). RNAi against dpy-27 , which encodes a DCC component, induced a more substantial rescue of male lethality, as expected (Meyer and Casson, 1986).…”
Section: Resultssupporting
confidence: 71%
“…As a result, the X chromosomes in hermaphrodites are highly compacted, occupying about 10% of the nuclear volume despite containing 18% of the genome (Lau et al, 2014). This compaction is also dependent on methylation at H3K9 (Snyder et al, 2016). We utilized this unique feature of the hermaphrodite X chromosomes to determine whether chromatin compaction is defective in morc-1(−) and hrde-1(−) mutants.…”
Section: Resultsmentioning
confidence: 99%
“…While a global analysis previously suggested that embryos of met-2 and met-2;set-25 are devoid of H3K9me3 [13], in germline-bearing met-2 adults, H3K9me3 was nevertheless detected [37,38]. In these studies, it was not examined whether dsRNAtriggered RNAi can induce H3K9me3 deposition on the targeted loci in the mutants.…”
Section: Resultsmentioning
confidence: 97%
“…LADs were initially reported to localize at the nuclear periphery, but single-cell analyses revealed that only a subset of LADs in the mammalian genome localizes to the lamina, whereas they are stochastically redistributed during the cell cycle between the lamina and the nuclear interior, where they tend to localize around nucleoli (Kind et al, 2013;van Steensel and Kind, 2014). A number of studies have shown that anchoring genes to the lamina correlates with tissue-specific gene repression (Gonzalez-Sandoval et al, 2015;Mattout et al, 2011;Meister et al, 2010;Robson et al, 2016;Therizols et al, 2014;Towbin et al, 2010) and dosage compensation (Snyder et al, 2016), leading to the concept that tethering of genomic regions to the lamina is required for stable repression of genes during differentiation (Amendola and van Steensel, 2014;Harr et al, 2016;Mattout et al, 2015).…”
Section: Regulation Of A-type Lamins In the Nuclear Interiormentioning
confidence: 99%